The Improvement of Modified Rice Straw Fiber/Polyvinyl Alcohol Thermoplastic Polymer Composite Using Cold Plasma Technology - Harianingsih, Harianingsih; Indriawan, Ari Nur Dwi; Setiadi, Rizki; Pangestu, Indra Sakti; Ubay, Isnina Noor; Erliana, Savira Rinda (Universitas Gadjah Mada, 2024)
The use of natural rice straw as a filler for composite materials has not been optimally utilized; only around 7–16% of the grain is used in the industry. Various developments have been carried out, including its use as a filler or reinforcement for wood polymer composite products, but it is not effective because of poor interfacial adhesion. An alternative to increase the effectiveness of straw fibers in wood composites is by using cold plasma (atmospheric) treatment. In this research, composites consisting of straw fiber and biodegradable polyvinyl alcohol (PVA) matrix were made with and without cold plasma injection treatment. PVA is used because of its hydrophilic nature and function as a matrix. This research aims to determine the effect of cold plasma injection on straw fiber/PVA composites. The method used consists of preparation of straw fiber and composites, flexural testing with time variations of 10, 20, and 30 sec, morphological analysis using SEM to determine surface roughness, and FTIR test. The results showed that treatment with and without plasma provided significant differences in roughness. Plasma causes roughness to increase, thereby increasing the adhesion of the interface to the matrix.